Quantum Information: An Introduction to Basic Theoretical Concepts and Experiments - Alber, Gernot; Beth, Thomas; Horodecki, Michal; Horodecki, Pawel; Horodecki, Ryszard; Roetteler, Martin; Weinfurter, Harald; Werner, Reinhard; Zeilinger, Anton (Springer Verlag, 2001)
The new technological prospects of processing quantum information are attracting not only physicists but also researchers from other communities, most prominently computer scientists. This book provides a self-contained introduction to the basic theoretical concepts, experimental techniques and recent advances in the fields of quantum communication, quantum information and quantum computation. In accordance with their interdisciplinary character, these central research topics in the emerging area of quantum technology are addressed both from the physical point of view and from the point of view of computer science, by leading experts. The introductory and self-contained character of the contributions should make this book particularly attractive to students and active researchers in physics and computer science who want to become acquainted with the underlying basic ideas and recent advances in the rapidly evolving field of quantum information processing.
Springer Tracts in Modern Physics